Answer:
See below
Step-by-step explanation:
I will describe this set in R³. Let P=(x,y,z) be a point equidistant to A and B, that is, the distance from P to A is equal to the distance from P to B.
First, using the usual distance formula, the distance from P to A is equal to [tex]d(P,A)=\sqrt{(x-(-3))^2+(y-6)^2+(z-3)^2}=\sqrt{(x+3)^2+(y-6)^2+(z-3)^2}[/tex]
On the other hand, the distance form P to B is equal to [tex]d(P,B)=\sqrt{(x-4)^2+(y-1)^2+(z-(-1))^2}=\sqrt{(x-4)^2+(y-1)^2+(z+1)^2}[/tex]
P is equidistant from A and B if and only if P satisfies the equation d(P,A)=d(P,B), that is,
[tex]\sqrt{(x+3)^2+(y-6)^2+(z-3)^2}=\sqrt{(x-4)^2+(y-1)^2+(z+-1)^2}[/tex]
Take the square in both sides of this equation to get
[tex](x+3)^2+(y-6)^2+(z-3)^2=(x-4)^2+(y-1)^2+(z+1)^2[/tex]
[tex](x+3)^2-(x-4)^2+(y-6)^2-(y-1)^2+(z-3)^2-(z+1)^2=0[/tex]
You can simplify using difference of squares and multiplying like this:
[tex](7)(2x-1)+(-5)(2y-7)+(-4)(2z-2)=0[/tex]
[tex]14x-10y-8z+36=0[/tex]
which is the equation of a plane.